2016
DOI: 10.19082/1832
|View full text |Cite
|
Sign up to set email alerts
|

The role of medicinal plants in the treatment of diabetes: a systematic review

Abstract: IntroductionDiabetes is a serious metabolic disorder and plenty of medical plants are used in traditional medicines to treat diabetes. These plants have no side effects and many existing medicines are derived from the plants. The purpose of this systematic review is to study diabetes and to summarize the available treatments for this disease, focusing especially on herbal medicine.MethodsRequired papers about diabetes and effective plants were searched from the databases, including Science direct, PubMed, Wile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
224
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(237 citation statements)
references
References 32 publications
2
224
0
11
Order By: Relevance
“…Many animal and human studies have reported that these plants can be useful in some disease and unhealthy conditions (5)(6)(7)(8). One of these medicinal plants is silymarin.…”
Section: Introductionmentioning
confidence: 99%
“…Many animal and human studies have reported that these plants can be useful in some disease and unhealthy conditions (5)(6)(7)(8). One of these medicinal plants is silymarin.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization has also recommended using herbal medicines (Committee, ). Plants are a rich source of flavonoids and antioxidants that studies have reported their efficacy and safety in improving hyperglycemia and management of diabetes as compared with synthetic drugs (Kooti, Farokhipour, Asadzadeh, Ashtary‐Larky, & Asadi‐Samani, ).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is known as 21 st century deadly disease and rank 5 th place in causing death in developed and developing countries (Kooti et al, 2016). Diabetes is a metabolic disorder due to lack of pancreases function in synthesis of insulin or resistance because of B cells damage.…”
Section: Introductionmentioning
confidence: 99%